The Rudgea hostmanniana complex (Rubiaceae) in the Guiana Shield region - Lachenaud, Olivier; Bruniera, Carla P.; Zappi, Daniela C. (Phytotaxa, 2022)
A taxonomic revision of the Rudgea hostmanniana complex in the Guiana shield region is presented. This group includes species with sheathing stipules bearing dorsal appendages, thick glabrous leaves lacking domatia, inflorescences thyrsoid to glomerulate but not regularly dichotomous, a calyx tube absent or very short, a corolla tube 2–7(–13) mm long, and fruits usually brownish when immature and turning red or orange at maturity. Eight species are recognized, among which Rudgea billietiae, endemic to Kaw Mountain in French Guiana, is newly described and illustrated; it is assessed as Endangered according to IUCN criteria. The other species are R. bolivarensis, R. cornigera, R. coussareoides, R. hostmanniana, R. maypurensis, R. pungens, and R. tanaosepala. A key to the species is presented, as well as a table summarising their diagnostic characters.